Fungsi Bahasa dalam Cerpen Berjuta Rasanya Karya Tere Liye: Perspektif Roman Jakobson - Luthfialana, Mawaddata; Hasyim, Muhammad; Al Anshory, Abdul Muntaqim (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2024)
The presence of language makes it easier for humans to interact as a means of communication. In its function, literary language can support the creative abilities of writers, and even become a language with artistic value. The aim of this research is to understand and describe the function of language contained in the short story "Berjuta Rasa" by Tere Liye. This research can help broaden understanding of Indonesian literary works, especially the short stories by Tere Liye. This research method is descriptive qualitative. The data collection technique in this research is by taking written sources, namely the short story "Berjuta Rasa" by Tere Liye with the aim of obtaining data as material for analysis. Based on the research results, six language functions were found based on Roman Jacobson's perspective as follows: 1) referential function; 2) emotional function; (3) poetic function; (4) phatic function; (5) conative function; (6) metalingual function;. This research enriches the theoretical understanding of the application of Roman Jakobson's language functions in literary works and provides practical guidance for readers and writers in understanding and utilizing linguistic elements to build meaning and emotion in short stories.  AbstrakKehadiran bahasa memudahkan manusia dalam berinteraksi sebagai alat komunikasi. Dalam fungsi bahasa sastra dapat mendukung kemampuan daya cipta sastrawan, bahkan sekaligus menjadi bahasa yang bernilai seni. Adapun tujuan dari penelitian ini adalah untuk memahami dan mendeskripsikan fungsi bahasa yang terdapat dalam cerpen Berjuta Rasanya karya Tere Liye. Penelitian ini dapat membantu memperluas pemahaman tentang karya sastra Indonesia, khususnya cerpen karya Tere Liye. Metode penelitian ini adalah deskriptif kualitatif. Teknik pengumpulan data dalam penelitian ini adalah dengan cara mengambil sumber tertulis yakni cerpen Berjuta Rasanya karya Tere Liye dengan tujuan memperoleh data sebagai bahan analisis. Berdasarkan hasil penelitian, maka ditemukan enam fungsi bahasa berdasarkan perspektif Roman Jakobson sebagai berikut: 1) fungsi referensial; 2) fungsi emosional; (3) fungsi puitis; (4) fungsi fatis; (5) fungsi konatif; (6) fungsi metalingual; Penelitian ini memperkaya wawasan teoritis tentang penerapan fungsi bahasa Roman Jakobson dalam karya sastra, serta memberikan panduan praktis bagi pembaca dan penulis dalam memahami dan memanfaatkan elemen linguistik untuk membangun makna dan emosi dalam cerpen.